2017
DOI: 10.14814/phy2.13454
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein improves the ability to detect cardiometabolic risk in mild-to-moderate obstructive sleep apnea

Abstract: Obstructive sleep apnea (OSA), particularly in the mild‐to‐moderate range, affects up to 40% of the adult general population. While it is clear that treatment should be pursued in severe cases of OSA, when and how to best treat OSA in the mild‐to‐moderate range remains complicated, despite its high prevalence. The aim of this study was to compare the relative utility of apnea/hypopnea index (AHI) versus a biomarker of inflammation, C‐reactive protein (CRP), in identifying the presence and severity of hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
1
2
2
Order By: Relevance
“…10,24 Among patients with OSA, BMI, sex, and anatomic characteristics such as neck circumference have been shown to be determinants of inflammation, and the addition of CRP to these clinical variables improves the detection of cardiometabolic conditions. [25][26][27][28][29] However, in contrast to previous findings, in our study the inclusion of CRP with patient characteristics (age, sex, BMI) did not increase the ability to detect hypertension, diabetes, and cardiac comorbidities in patients with OSA. Determinants of elevated CRP and PSG variables have been previously studied although they remain less clear, with some studies showing a positive association between CRP and AHI.…”
Section: Discussioncontrasting
confidence: 99%
“…10,24 Among patients with OSA, BMI, sex, and anatomic characteristics such as neck circumference have been shown to be determinants of inflammation, and the addition of CRP to these clinical variables improves the detection of cardiometabolic conditions. [25][26][27][28][29] However, in contrast to previous findings, in our study the inclusion of CRP with patient characteristics (age, sex, BMI) did not increase the ability to detect hypertension, diabetes, and cardiac comorbidities in patients with OSA. Determinants of elevated CRP and PSG variables have been previously studied although they remain less clear, with some studies showing a positive association between CRP and AHI.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with previous studies, hsCRP also was found to be higher among patients with severe OSA in the present research [40]. According to the previous studies hsCRP has been found to be associated with cardiovascular risk factors such as obesity, hyperglycemia and hypertension [41]. In our study these factors were not significantly different among OSA groups.…”
Section: Discussionsupporting
confidence: 92%
“…Elevated CRP levels were associated, even to a greater extent than SDB, with SBP and fasting glucose levels. (Gaines et al, 2017) We speculate that the mitigating effect in our present study between hypertension and hyperglycaemia, the former positively whereas the latter negatively associated with hyperuricaemia, negates the association of objective disrupted sleep or high CRP levels with hyperuricaemia. On the other hand, estimated anaerobic thresholds (continuous data) were inversely associated with serum UA levels (continuous data) in people with chronic heart failure (Leyva, Chua, Anker, & Coats, 1998).…”
Section: Discussioncontrasting
confidence: 50%